Complex evaluation of serum immunoglobulin levels in patients with chronic lymphocytic leukemia: Significant increase in IgA after first-line chemoimmunotherapy - Vodárek, Pavel; Écsiová, Dominika; Řezáčová, Vladimíra; Souček, Ondřej; Šimkovič, Martin; Vokurková, Doris; Belada, David; Žák, Pavel; Smolej, Lukáš (Cancer medicine, 2024)
INTRODUCTION: The impact of chemoimmunotherapy (CIT) on immunoglobulin (Ig) quantities in patients with chronic lymphocytic leukemia (CLL) has not been extensively studied. METHODS: We analyzed Ig levels in 45 stable patients with indolent CLL (without indication for treatment) and 87 patients with progressive disease before first-line treatment. Fifty-five patients were evaluated again after the treatment with CIT. RESULTS: We observed significantly lower levels of all Ig classes and subclasses in patients with progressive disease compared to patients with indolent disease. After treatment, median IgA increased from 0.59 g/L to 0.74 g/L (p = 0.0031). In stable patients, lower IgA2 was associated with shorter time to first treatment, although it did not reach statistical significance (p = 0.056). Shorter overall survival was observed in patients with progressive disease and lower IgG2 (p = 0.043). Surprisingly, among the patients with progressive CLL, unmutated IGHV genes were associated with higher levels of IgG, IgG1 and IgM, while TP53 mutation and/or 17p deletion were associated with higher levels of IgA and IgA1. CONCLUSIONS: CIT may lead to increase in IgA levels. Hypogammaglobulinemia is more common in patients with progressive CLL and unmutated IGHV or TP53 dysfunction.
Keywords: Disease Progression; lidé; Middle Aged; Adult; imunoterapie; immunoglobulin; infections; prognosis; Female; CLL; progrese nemoci; Humans; protokoly protinádorové kombinované chemoterapie; lidé středního věku; Immunotherapy; mužské pohlaví; immunosuppression; ženské pohlaví; Aged, 80 and over; imunoglobulin A; senioři nad 80 let; Male; Aged; chronická lymfatická leukemie; chemoimmunotherapy; Immunoglobulin A; dospělí; Antineoplastic Combined Chemotherapy Protocols; Leukemia, Lymphocytic, Chronic, B-Cell; senioři